A comprehensive assessment framework for quantifying climatic and anthropogenic contributions to streamflow changes: A case study in a typical semi-arid North China basin. (June 2020) - Zhang, Ke; Ruben, Gebdang B.; Li, Xin; Li, Zhijia; Yu, Zhongbo; Xia, Jun; Dong, Zengchuan
Abstract: This study proposes to jointly use six Budyko framework-based methods, hydrological simulation, sensitivity indicator method, and empirical statistics to build a comprehensive assessment framework for quantifying climatic and anthropogenic contributions to streamflow changes. To evaluate its effectiveness, we conducted a case study in a typical northern semi-arid basin named Guanting in China. On average, human activities and climate change account for 80.22–81.51% and 18.49–19.78% of the streamflow decline in the two subbasins, i.e ., Shixiali and Xiangshuipu, of the study basin during the 1984–1999 and 2000–2015 periods, respectively. Precipitation change outweighs potential evapotranspiration change as a primary climatic contributor of streamflow reduction in the two subbasins. In Xiangshuipu, the average precipitation elasticity of streamflow ( ε P ) is 2.48 ± 0.23 and 2.56 ± 0.28 for the 1984–1999 and 2000–2015 periods, respectively, while ε P in Shixiali has an average ε P value of 2.49 ± 0.31 and 2.66 ± 0.32 during the two periods. Difference between the ten attribution methods varies between 5% and 12%, highlighting importance of applying this developed multi-method framework to avoid overestimation/underestimation and quantify uncertainty. This proposed comprehensive change attribution method is valuable for quantitatively distinguishing the relative contributions of external factors on hydrological regime changes. Highlights: Developed a new framework quantifying climatic and human impacts to streamflow. Budyko-based methods, modeling, sensitivity and empirical analyses were jointly used. Human activities caused more streamflow reduction than climate change in Guanting. The impacts of human activities on runoff have increased over time in Guanting. Streamflow in Guanting is more sensitive to precipitation than other climatic factors.